1996
DOI: 10.1016/0042-6989(95)00190-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of display size on disparity scaling from differential perspective and vergence cues

Abstract: The present study compared the relative effectiveness of differential perspective and vergence angle manipulations in scaling depth from horizontal disparities. When differential perspective and vergence angle were manipulated together (to simulate a range of different viewing distances from 28 cm to infinity), approximately 35% of the scaling required for complete depth constancy was obtained. When manipulated separately the relative influence of each cue depended crucially on the size of the visual display. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 13 publications
5
77
0
Order By: Relevance
“…It has long been established that both cues can evoke independently a strong impression of depth structure (1,2) and determine relative depth with immense precision (3) . The degree to which either cue supports veridical judgments of an object's size and depth, however, has been questioned in a recent, well-focused sequence of experiments on depth constancy and shape perception (3)(4)(5)(6)(7)(8)(9)(10)(11) . The general conclusion of these experiments is that depth constancy is considerably less than perfect, perceived shape is distorted and absolute distance is typically misestimated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been established that both cues can evoke independently a strong impression of depth structure (1,2) and determine relative depth with immense precision (3) . The degree to which either cue supports veridical judgments of an object's size and depth, however, has been questioned in a recent, well-focused sequence of experiments on depth constancy and shape perception (3)(4)(5)(6)(7)(8)(9)(10)(11) . The general conclusion of these experiments is that depth constancy is considerably less than perfect, perceived shape is distorted and absolute distance is typically misestimated.…”
Section: Introductionmentioning
confidence: 99%
“…To recover veridical depth structure, initial measurements of horizontal binocular disparity and retinal image motion must be scaled using additional (e.g. extra-retinal) information or, if both cues are available simultaneously, this scaling problem can be avoided as there is sufficient information in the retinal image to determine structure and viewing distance uniquely through the combination of the information that each cue provides (3,10,12,13) . Whether perceptual performance improves when both cues are available simultaneously remains uncertain (3,(14)(15)(16)(17) see also Landy & Brenner (18) for a recent review).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that vertical disparity patterns can have a strong influence on frontal plane judgements, particularly for large field of view displays 18 . If a viewer fixates a point on a fronto-parallel screen then, at all distances nearer than infinity, the images of other points on the screen have horizontal disparity.…”
Section: Vertical Disparity In Toed-in Stereoscopic Camerasmentioning
confidence: 99%
“…Vertical disparities have been shown to be effective in the scaling of depth, shape and size from disparity 12,18 . When the cameras are toed-in the vertical disparities indicate a nearer surface.…”
Section: Do the Toed-in Configurations Improve Depth And Size Scaling?mentioning
confidence: 99%
See 1 more Smart Citation